2017
DOI: 10.4081/idr.2017.6930
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Complication Patterns of Influenza A (H1N1 Virus) in Northern Saudi Arabia

Abstract: The aim of the present study is to describe epidemiologic and clinical presentation, clinical complications and outcomes of patients diagnosed with influenza A infection (H1N1) during a one-year period. We retrospectively investigated 300 patients with influenza-like clinical presentation during the period January 2015 – January 2016 in King Khalid Hospital, Saudi Arabia. Fifty-four patients out of 300 (18%) were diagnosed with H1N1 virus infection; their age ranged from 7 months to 85 years, with a mean age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In Hail City, a retrospective study conducted throughout 2015 at King Khaled Hospital revealed 54 (18%) infections with H1N1 pdm09. The patients ranged in age from 7 months to 85 years [78]. In a prospective study conducted from June to November of 2009, 526 health care workers at King Abdulaziz Medical City (Riyadh) tested positive for H1N1 pdm09 [79].…”
Section: Epidemiologymentioning
confidence: 99%
“…In Hail City, a retrospective study conducted throughout 2015 at King Khaled Hospital revealed 54 (18%) infections with H1N1 pdm09. The patients ranged in age from 7 months to 85 years [78]. In a prospective study conducted from June to November of 2009, 526 health care workers at King Abdulaziz Medical City (Riyadh) tested positive for H1N1 pdm09 [79].…”
Section: Epidemiologymentioning
confidence: 99%
“…Of the H1N1-positive patients, 8 (14.8%) developed pneumonia, 5 (9.3%) developed adult respiratory distress syndrome, 15 (27.8%) required ICU admission, and 9 (16.6%) required mechanical ventilation. This study involved both adult and pediatric patients, and no comparison with the H1N1negative patients was noted [16].…”
Section: Comparison Between H1n1 Pcr-positive Patients and H1n1 Pcr-nmentioning
confidence: 99%
“…The outbreak of H1N1 influenza infection in Saudi Arabia has become an inevitable pediatric infectious disease, which requires huge public health attention and treatment strategy (Alsufiani et al, 2014); Altayep et al, 2017). The pandemic outbreaks of H1N1 recorded in the European Union (EU) and other parts of the world as per the WHO records known to have a potential impact on the health, social and economic conditions of the society (Stoto, 2017).…”
Section: Introductionmentioning
confidence: 99%